EFFECTIVENESS OF ONLINE LEARNING AND FACE-TO-FACE LEARNING ON STUDENTS - Dolfina Costansah Koirewoa; Didik Cahyono; Erwin (CV. ADIBA AISHA AMIRA, 2024)
The degree to which learning outcomes are attained during the teaching and learning process is demonstrated by the condition of learning effectiveness. Online learning uses the internet network to facilitate learning without requiring students and teachers to interact face-to- face. According to the research findings, there was little difference in the learning outcomes of students before and during the epidemic. This demonstrates that studying through WhatsApp and Google Classroom is thought to be highly successful. Learning both in person and online is a topic that is frequently debated. not just with pupils but also with parents. A lot of people search for the best learning experience by comparing the two learning systems. While some believe that face-to- face communication is superior, others believe that online communication is superior. It's critical to understand the benefits and drawbacks of each approach since they each have unique advantages and downsides. The literature study method is being used in this investigation. Definitions of online and in-person learning, benefits of both types of learning, and distinctions and parallels between online and in-person teaching approaches are all covered in this study